Late Middle Stone Age Behavior and Environments at Chaminade I (Karonga, Malawi) - Nightingale, Sheila; Schilt, Flora; Thompson, Jessica C.; Wright, David K.; Forman, Steven; Mercader, Julio; Moss, Patrick; Clarke, Siobhan; Itambu, Makarius; Gomani-Chindebvu, Elizabeth; Welling, Menno (Journal of Paleolithic Archaeology, 2019)
The African Middle Stone Age (MSA, typical range ~ 320–30 ka) has been the subject of intense research interest in recent decades as a culture-chronological Unit associated with the emergence and dispersal of our species. Recent results of this work have shown that sites designated as “MSA” contain common approaches to lithic reduction, but that within this rubric, there is much diversity in overall assemblage characteristics and the timing of their appearance across the continent. As researchers recover more data from more sites, especially from undersampled geographic regions, this more complex picture of the MSA reveals technological and other behavioral diversity in early modern human populations that may inform about the ultimate success of our species. Here we add to this growing database by describing the environmental context and characteristics of two concentrations of stone artifacts from the late MSA (~ 43–21 ka) open-air locality of Chaminade-I (CHA-I), near the town of Karonga in northern Malawi. The CHA-I lithic artifacts show a flexible approach to stone tool production and use that is common to assemblages in Karonga but distinctive from MSA sites reported elsewhere. Radial and minimally reduced cores typify an unelaborated lithic assemblage, in which raw material choice is driven by toolstone clast size and shape rather than preferential use or treatment of specific materials, as found in MSA assemblages in the East African Rift, South Africa, and the North African coast. Lithic reduction at CHA-I took place within a woody, riparian context embedded within a more open woodland landscape. Most artifacts occurred in near-channel sandy deposits dated to ~ 41 ka, and were buried under alluvial fan deposits that began aggrading by at least ~ 21 ka and continued beyond ~ 5.5 ka within a grassy, open landscape. The site’s late MSA age and lack of elaboration in lithic technology challenges straightforward ideas of increasing complexity in human technological behavior over time and provides important insight into the diversity of MSA technologies and the environmental conditions in which they existed.